'Being human' and the 'moral sidestep' in drug policy: Explaining government inaction on opioid-related deaths in the UK. (March 2019) - Stevens, Alex
Abstract: Background: With drug-related deaths at record levels in the UK, the government faces two potential sources of pressure to implement more effective policies. One source is the individuals and families who are most likely to suffer from such deaths; i.e. working class people living in de-industrialised areas. The other source is experts who argue for different policy on the basis of research evidences. Aim: This article aims to explain why, in the face of these two potential sources of pressure, the UK government has not implemented effective measures to reduce deaths. Method: The article uses critical realist discourse analysis of official documents and ministerial speeches on recent British drug policy (2016–2018). It explore this discourse through the theoretical lens of Archer's (2000) ideas on 'being human' and by drawing on Sayer's (2005) work on the 'moral significance of class'. Results: Members of economically 'residual' groups (including working class people who use heroin) are excluded from articulating their interests in 'late welfare capitalism' in a project of depersonalising 'class contempt' through which politicians cast the people most likely to die as passive, 'vulnerable' 'abjects'. Conservative politicians dismiss 'evidence-based' ideas on the reduction of drug-related death through a 'moral sidestep'. They defend policy on the basis of its relevance to conservative moral principles, not effectiveness. This is consistent with the broader moral and political pursuit of partial state shrinkage which Conservative politicians and the social groups they represent have pursued since the 1970s. Highlights: The UK has its highest ever levels of drug-related death, but the government is not using effective measures to reduce deaths. The people most likely to die are working class, middle-aged people living in de-industrialised areas. Analysis of official discourses shows that these people are denied fully human agency. Efforts to use evidence to change policy are met with a 'moral sidestep' towards conservative values of purity and conformity.